The Effect of Training and Compensation on Performance Employees With Motivation As A Mediation Variable - Abdul Hakim; I Ketut Sudiardhita; Henry Eryanto (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2020)
Training and compensation programs are provided by the company to motivate employees and improve employee performance. This study aims to analyze the effect of training and compensation on employee performance using motivation as mediation at PT. Servistama Pacific Sedana. This research uses a quantitative approach with the observation unit of all employees of PT. Sedana Pasifik Servistama and total sampling technique with a total of 110 respondents. The method used is a survey using a questionnaire and descriptive research type explanatory research. This research's data analysis method is the validity test, reliability test, and hypothesis test using SEM (Structural Equation Modeling). The results showed that training and compensation had a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance. Motivation can mediate the effect of training on employee performance and motivation to mediate the effect of compensation on employee performance at PT. Servistama Pacific Sedana.